Safe Haven CDS Premiums - Klingler, Sven; Lando, David (Review of Financial Studies, 2018)
Credit default swaps can be used to lower the capital requirements of dealer banks entering into uncollateralized derivatives positions with sovereigns. We show in a model that the regulatory incentive to obtain capital relief makes CDS contracts valuable to dealer banks and empirically that, consistent with the use of CDS for regulatory purposes, there is a disconnect between changes in bond yield spreads and in CDS premiums, especially for safe sovereigns. Additional empirical tests related to the volume of contracts outstanding, effects of regulatory proxies, and the corporate bond and CDS markets support that CDS contracts are used for capital relief. (